Contribution of Arnett's Inventory of Sensation Seeking and Zuckerman's Sensation Seeking Scale to the differentiation of athletes engaged in high and low risk sports - Zarevski, Predrag (Array, 1997)
AISS (Arnett, 1994) and Zuckermans SSS scales were adiminstered on 94 pairs of males between 17 and 47 years of age (M = 29.6 years). Pairs were equivalent in age and education. Independent variable is risk level of the sports they are engaged in (high risk sports were parachute jumping, diving, gliding, speleology and free climbing, while low risk sports were athletics, rowing, bowling and table tennis). The aim was identify out which of these two scales is better at discriminating the two groups of athletes, since this is an important test of criterion validity for these two operationalizations of sensation seeking construct. According to the univariate F ratios, all six predictors significantly differentiated the criterion groups on p < 0.01 level, while in discriminant analysis all the valid discriminant variance was accounted for by only two Zuckermans subscales - TAS and ES.